Along Voortrekker Road - Ravel, Clotilde (WritingThreeSixty, 2018)
These three photographs were taken on Wednesday, 27th April 2016. I chose to shoot on a cloudy and misty day in three locations along Voortrekker Road: Parow, Maitland and Salt River. The weather was changing quite rapidly - from cloudy to sunny, and this constituted a challenge because I wanted to have the same atmosphere in the three pictures. I followed the course of the clouds, hoping they would not allow the sun to shine through the clouds. I used a black and white filter because it allows for a larger range of emotions and conveys an impression of timelessness.